Addition of Sodium Hyaluronate to Ringer Lactate-Egg Yolk Diluent on the Quality of Native Chicken Sperm - Khaeruddin, Khaeruddin; Fattah, Abdul Hakim; Syamsuryadi, Bahri; Hermawansyah, Hermawansyah (Jurnal Agripet, 2025)
This study aims to evaluate the effect of adding varying concentrations of sodium hyaluronate (SH) to a Ringer lactate-egg yolk diluent on the quality of native chicken spermatozoa during 48 hours of storage. A completely randomized design (CRD) was used with four treatment groups: control (diluent without SH), diluent with 63 M SH, 103 M SH, and 143 M SH. The study involved six replications with pooled semen from three native chickens aged approximately 10 months. Semen was collected, diluted, and stored at 5C for 48 hours. Parameters observed after storage included motility, viability, plasma membrane integrity, acrosome integrity, DNA damage, and mitochondrial activity. Data were analyzed using analysis of variance (ANOVA). The results indicated that the treatments had no significant effect (P0.05) on any of the spermatozoa quality parameters. The observed values for motility, viability, plasma membrane integrity, acrosome integrity, DNA damage, and mitochondrial activity were 46.67-50%, 95.11-96.55%, 92.77-95.55%, 4.77-5.44%, and 71.05-75.37%, respectively. In conclusion, the addition of sodium hyaluronate at concentrations of 63-143 M in a Ringer lactate-egg yolk diluent does not significantly affect the quality of native chicken spermatozoa during 48 hours of storage at 5C.